2020
DOI: 10.12669/pjms.36.covid19-s4.2829
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and demographical profile of Coronavirus illness: The tale of Tablighi Jamaat and Zaireen in Quarantine / Isolation center at Sukkur and Hyderabad

Abstract: Objectives: To determine the clinical and demographical profile of corona-virus illness among Tablighi Jamaat and Zaireen kept in quarantine / isolation center at Sukkur and Hyderabad Sindh. Methods: The cross-sectional descriptive study (late March-2020 to mid of April-2020) was conducted at Diagnostic & Research Laboratory LUMHS Jamshoro / Hyderabad. All the suspected cases for COVID-19 were recruited and screened for corona virus infection. The study explored the data of the suspected and diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Previous studies provide limited evidence on the clinical characteristics of SARS-CoV-2 infection in Pakistan [31][32][33][34][35][36][37][38][39][40][41][42][43]. These studies had several limitations, including a small sample size or data collection at a single diagnostic center.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies provide limited evidence on the clinical characteristics of SARS-CoV-2 infection in Pakistan [31][32][33][34][35][36][37][38][39][40][41][42][43]. These studies had several limitations, including a small sample size or data collection at a single diagnostic center.…”
Section: Resultsmentioning
confidence: 99%
“…In the diagnosis of COVID-19, reverse transcriptase polymerase chain reaction (RT-PCR) test on respiratory samples is accepted as the gold standard. 1 - 3 However, the sensitivity is reported as low as 59-71%, because of possible false negative with the RT-PCR test due to insufficient viral material in the sample or a procedural error. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another investigation showed a clear association between smoking and disease severity, with approximately 3% of deceased patients being smokers. 52 Moreover, a meta-analysis that included 7 studies found that smokers had twice the risk of developing COVID-19 severity. 53 …”
Section: Discussionmentioning
confidence: 99%